Meloidogyne incognita and melon plants: host status, induced resistance and biological control - Souza, Victor Hugo Moura de (2019)
The melon crop (Cucumis melo L.) is the most exported fruit of Brazil and consist in an important agribusiness to the producers on Northeastern Region of Brazil, having as the main producers the Rio Grande do Norte and Ceará states. Among the limiting factors of this crop, root-knot nematode (Meloidogyne spp.) stand out a major treat, that causes on severed attacked plants malnourishment, poor development of the above-ground portion and shorter root system due to the galls, which is the most characteristic symptom of this disease. With the lack of management tools to the root-knot nematode, alternative measures are needed to avoid losses. In this context, the main objective of the present work was to evaluate the influence of resistance inducers and biological control agents on the control of M. incognita on melon plants, as the influence of these agents on melon plant development and their effects on different M. incognita stages. For these purposes, greenhouse experiments were performed. The first one aimed to verify the host status of melon hybrids to M. incognita and additional three were carried out to verify the influence of resistance inducers and biological control organisms on melon development and on the control of M. incognita on this crop (trials #1, #2 and #3). Also, an additional greenhouse trials were carried out to verify different doses of P. chlamydosporia (Rizotec® ) on the control of M. incognita in melon plants and to verify the potential of culture filtrates (Cf) obtained from biological control organisms on the control of M. incognita and on the melon plant development. In these greenhouse experiments, the reproductive variables final population (Pf), reproduction factor (R value) and nematodes per gram of root (Nem/g) were obtained at the end of the experiments. Additionally, it was evaluated the fresh and dry weight of the aerial portion, the plant height, root weight, fruit weight, stem diameter (measured on stem basis, middle and apex) and chlorophyll content. Additionally, in vitro assays were performed to verify the effect of Cfs on melon seeds and to verify the effect of the Cfs and the partially purified thaxtomin A (PPT) on M. incognita egg hatching. Moreover, three additional assays were carried out to verify the effect of resistance inducers acibenzolar-S-methyl (ASM) and PPT in the penetration and post-penetration of M. incognita second stages juveniles in melon roots. As results, all tested genotypes were susceptible to M. incognita. The Pf values ranged from 2,381.06 to 7,806 nematodes, the R value ranged from 5.95 to 19.5. Also, nem/g values ranged from 271 to 1,791. In trial #1, melon plants treated with resistance inducers presented lower height; despite no statistically differences were found for fresh and dry weight. Also, plants treated with ASM (inoculated and non-inoculated), Paecilomyces lilacinus, (non-inoculated) and Pochonia chlamydosporia (inoculated) produced heavy fruits. On trial #2, all inoculated plants differed statistically on root weight and presented heavier roots than non-inoculated plants, which was due the large amount of galls caused by M. incognita. In addition, treated plants with the biological control agents presented fewer symptoms than control plants. Treated melon plants exhibited higher chlorophyll content on young leaves, when compared with both controls. Moreover, on both treatments the M. incognita population was reduced, except by P. chlamydosporia on the experiment 1. When tested separately, all P. chlamydosporia doses reduced the Pf, however the most efficient were the dose 4 (1g/plant) and dose 5 (2g/plant). Regarding Cf, promising results were obtained. Both Cf from P. lilacinus and Bacillus amyloliquefaciens reduced the M. incognita population, in greenhouse experiment. Additionally, P. lilacinus Cf increased the fruit weight, and B. amyloliquefaciens Cf increased the root weight, despite being inoculated or not. Furthermore, the tested Cfs presented suppressive effect on M. incognita egg hatching, but further evidence is necessary due to lack of statistical differences with the potato-dextrose broth medium (PD). Additionally, the filtrates improved the germination of melon seeds, despite the suppressed effect of PD broth medium on them. Also,i> P. chlamydosporia treatment induced hairy roots, which were not observed on the other treatments. Regarding the penetration assays, juveniles were not observed at 3 days after inoculation (DAI). No effect of ASM in penetration and post-penetration of M. incognita J2 was 13 observed on both experiments. Concerning PPT, penetration was not observed at 3 DAI, but it was observed on the other assessed periods. Furthermore, our data points out that the TPP may speed the nematode cycle on melon roots. In conclusion, the obtained data point out the potential of the resistance inducers, biological control organisms and their culture filtrates on the control of M. incognita on melon plants.